The impact of ranibizumab on the level of intercellular adhesion molecule type 1 in the vitreous of eyes with proliferative diabetic retinopathy. (18th August 2015) - Yan, Ying; Zhu, Li; Hong, Ling; Deng, Jun; Song, Yanpin; Chen, Xiao
Abstract: Purpose: This study was to investigate the impact of ranibizumab on the level of intercellular adhesion molecule type 1 (ICAM‐1) in the vitreous of eyes with PDR. Methods: This is an interventional case–control study. A total of 82 eyes from 82 patients who had undergone vitreous surgery for the treatment of retinal disorders were included. Twenty‐two eyes with PDR received an intravitreal ranibizumab injection (IVR) 3–7 days before vitrectomy and were grouped as 'PDR with recent IVR' or Group 1. Sixteen eyes with PDR received IVR more than 7 days before vitrectomy and were grouped as 'PDR with remote IVR' or Group 2. Twenty‐two matched PDR eyes did not receive IVR before vitrectomy and were grouped as 'PDR without IVR' or Group 3. Finally, 22 eyes from 22 patients with idiopathic macular pucker (IMP) served as the 'non‐diabetic control' group, or Group 4. Vitreous samples were obtained at the time of vitrectomy from all eyes, and the levels of vascular endothelium growth factor (VEGF) and ICAM‐1 were analysed using ELISA. Results: PDR without IVR (Group 3) had the highest vitreous VEGF concentration; the difference was significant compared with those in the PDR with recent IVR (Group 1), PDR with remote IVR (Group 2) and the non‐diabetic control group (Group 4) (p < 0.001). Group 2 had a lower vitreous VEGF level than Group 1 (p = 0.041). Group 1 had the highest vitreous ICAM‐1 levels (p < 0.001 versus. Groups 2, 3 and 4); Group 2 had a lower vitreous ICAM‐1 level than Group 3 (p = 0.028). Conclusion: The vitreous fluid level of ICAM‐1 was significantly increased within 1 week of IVR administration, but markedly decreased after a week of administration in eyes with PDR. This suggests that leucostasis, vascular leakage and endothelial dysfunction may be amplified in the early days after IVR, but that a therapeutic effect of IVR in these processes may appear after 1 week of ranibizumab administration in eyes with PDR.